On the Issue of Sense Benchmarks of Behavior (Economic-Legal Aspects) - DUDCHENKO, Valentina V.; TSURKAN-SAIFULINA, Yuliia V.; TSURKAN, Oleksandr V. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).05, 2019)
This paper attempts to analyze the leakages, essence, the peculiarity of normative meanings and their connection with public values. From the ability to cognize ‘that to which to aspire to’, a person becomes capable to understand a meaning of deeds. To solve a practical question in the legal sphere, that means to say what is proper. The authors have proved the difference between analytical judgments a posteriori and, thus, justified the method's reform and the need for a holistic consideration of all things, including legal, in epistemology. It is revealed that the method of describing the meaning is hermeneutics and that the peculiarity of the teleological (target) interpretation is the orientation towards the goal, on the principles. The opportunity to motivate actions through normative meanings is substantiated.